Detection of Rhodamine B in Tomato Sauce Distributed by Street Food Vendors in Kambu District, Kendari City - Abdul Rahman; Tanri Yunanto Widodo; Widarni; Magvirah Tuljannah; Nadia Dwiharja Musrin; Hikma Sri Nurwidiarni; Ramadhan Tosepu; Asramid Yasin (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Rhodamine B is a bright red synthetic dye that is toxic and carcinogenic, and therefore its use in food is prohibited by the Food and Drug Supervisory Agency (BPOM). However, illegal use of this substance is still found, especially in foods sold freely such as those from street vendors. Objective: This research aims to analyze the presence of Rhodamin B content in tomato sauce used by street vendors on Haluoleo Street, Kambu Village, Kendari City, and relate it to the characteristics of vulnerable consumers. Methods: This research uses a quantitative descriptive design with laboratory tests using test kits. The samples in this study consist of five types of ketchup obtained from five different street vendors along Jl. Haluoleo, Kambu, City of Kendari. Results: The test results show that all negative samples contain Rhodamine B, which indicates that the food sauces sold at that location are relatively safe for consumption. From the respondents' perspective, the majority belong to the young age group (18–21 years) with varying weight distribution, and most are men who claim to regularly consume food from street vendors. Although the test results indicate no presence of Rhodamine B, the risk of exposure to hazardous substances still exists if monitoring and consumer education are not improved. Conclusion: Nickel mining in North Konawe Regency has brought positive economic impacts, such as increased production and employment opportunities. However, it has also led to river pollution due to industrial waste containing heavy metals, which affects water quality and public health. Therefore, proper environmental management and the preparation of a comprehensive Environmental Impact Assessment are essential to minimize negative impacts and support the sustainability of mining activities.